Dakwah Issues: Introduction to Values and Activities of Interpersonal Ethic - Razaleigh bin Muhamat (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2006)
Discourses of intepersonal ethic have found many mistakes, especialy for those who do not believe in religion as the way of We, ike in the West This article presents altenatives of value and activity in interpersonal ethic using in the pluralistic society, ike Malaysia. texplains the background of value and activily of interpersonal ethic from ts source, meaning, activity base and its significance.it adds with discourses from previous scientist. It seems similar the Islamic discourse of interpersonal ethics with the discourse of Moslem personalities. The main purpose of interpersonal ethic discourse is to find the able term to analize interpersonal ethic it self At the end of the article, it explains the parts of interpersonal activities which are important for everybody, especially for Dai in their feld